Traditional Music in Pop's Grip: The Congdut Evolution and Regional Music Transformation by Jujuk Eksa - Dony Hutomo Ardi; Eko Raharjo (Jurnal Seni Musik, 2025)
This research examines the evolution of Indonesian traditional music in response to the influence of globalization and technological advancements, with a focus on the emergence of the Congdut genre as a result of the hybridization between dangdut and keroncong, initiated by Jujuk Eksa. Through a descriptive qualitative approach, incorporating observation, interviews, and documentation techniques at JX Studio, Demak, this study analyzes the creative process, musical structure, and artistic philosophy behind the creation of Congdut. The survey results show that Congdut is not just a mixture of two genres, but a form of third space that combines the rhythmic energy of dangdut with the harmonious complexity of keroncong, thereby creating a dynamic and relevant new cultural identity. Congdut acts as a revitalization strategy to overcome the stagnation of keroncong music while cleaning the image of dangdut from social stigma. Its socio-cultural implications reflect the ability of traditional music to adapt and survive in the modern era through a creative dialogue between tradition and modernity. The sustainability of Congdut depends on its adoption by the younger generation, integration into digital platforms, and the potential for integration into music education.